Experimental measurement of forces during percutaneous dilatational tracheostomy. (April 2018) - Pancani, Silvia; Virga, Antonio; Spina, Rosario; Peris, Adriano; Corvi, Andrea
The measurement of mechanical effects associated with the dilatation phase of a percutaneous dilatational tracheostomy is of primary importance to identify the causes of major complications associated with this procedure, such as tracheal cartilage subluxation or fracture and bleeding. Such information can be very useful also for the design of better instruments and procedures. The aim of this study was to present a methodology to evaluate mechanical effects of the dilatation phase of a percutaneous dilatational tracheostomy on the tracheal rings and adjacent anatomical structures. Forces and moments were measured through a dilator instrumented with strain gauges. Two surgeons, with different levels of expertise, performed the percutaneous dilatational tracheostomy on a lifelike reproduction of an adult head, specifically designed for training professionals. The modified dilator was effective in measuring forces involved in the percutaneous dilatational tracheostomy without affecting the ability of the operator to perform the procedure. The main contribution to the insertion of the dilator was given by the axial force, defined as the force acting on the handle, compressing it (mean and peak force: 48.8 and 88.2 N for Surgeon 1, 31.3 and 82.8 N for Surgeon 2, respectively). The proposed method was effective in measuring differences between procedures performed by surgeons with different amounts of experience in terms of duration, forces applied and repeatability. In addition, it may have applications for use as a feedback for incorrect positioning or excessively variable pressure during the training of surgeons for the execution of percutaneous dilatational tracheostomy.